2010
DOI: 10.2139/ssrn.1555652
|View full text |Cite
|
Sign up to set email alerts
|

Information Asymmetries and the Value-Relevance of Cash Flow and Accounting Figures – Empirical Analysis and Implications for Managerial Accounting

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Further, senior and middle managers could adopt up-to-date cost techniques to tackle unexpected operational efficiency and to take sound pricing decisions in different activities of corporations (Dutta & Gigler, 2002, p. 15;Monroy, Nasiri, & Pelaez, 2012, p. 21). Besides, limited studies pointed to the role of costing systems based on time driven activities to strengthen relationships between TDABC and related variables, such as pricing decisions, efficiency and effectiveness, cost benefit analysis, profitability and competitiveness where the applicationad and intehrations between them can provide benefits to all parties interested in corporations (Kaplan & Anderson 2007, p. 15;Rapp, 2010;Al-Halabi, 2016, p. 55;Hilton, 2008, p. 231;Lin, 2012, p. 14).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, senior and middle managers could adopt up-to-date cost techniques to tackle unexpected operational efficiency and to take sound pricing decisions in different activities of corporations (Dutta & Gigler, 2002, p. 15;Monroy, Nasiri, & Pelaez, 2012, p. 21). Besides, limited studies pointed to the role of costing systems based on time driven activities to strengthen relationships between TDABC and related variables, such as pricing decisions, efficiency and effectiveness, cost benefit analysis, profitability and competitiveness where the applicationad and intehrations between them can provide benefits to all parties interested in corporations (Kaplan & Anderson 2007, p. 15;Rapp, 2010;Al-Halabi, 2016, p. 55;Hilton, 2008, p. 231;Lin, 2012, p. 14).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investors will face high information risk associated with the information asymmetry problem and they will push down the stock price or request higher cost of capital to compensate for the information risks because they are rational players in the capital market (Easley and O'Hara, 2004;Gray et al, 2008). Several prior studies have confirmed that the association between accounting information and stock pricing varies when there is a difference in the degree of information asymmetry between firm managers and external investors (Rapp, 2010;Choi et al, 2011;Cormier et al, 2011;Hilary and Shen, 2013).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Steffen Rapp (2010) in his research investigated the relationship between accounting earnings and cash flows and shareholders' return under the condition of information asymmetry. According to the results, under the condition of information asymmetry, accounting earnings have more information content than cash flows.…”
Section: Theoretical Foundations Of the Studymentioning
confidence: 99%